Cobalt-Based Electrocatalysts for Sustainable Nitrate Conversion: Structural Design and Mechanistic Advancements - Chang, GuoLiang; Chen, Xueqiu; Lv, Jing‑Jing; Kong, Zhijie; Wang, Zheng‑Jun (Nano-Micro Letters, 2025)
Electrocatalytic nitrate-to-ammonia conversion offers dual environmental and sustainable synthesis benefits, but achieving high efficiency with low-cost catalysts remains a major challenge. This review focuses on cobalt-based electrocatalysts, emphasizing their structural engineering for enhanced the performance of electrocatalytic nitrate reduction reaction (NO3RR) through dimensional control, compositional tuning, and coordination microenvironment modulation. Notably, by critically analyzing metallic cobalt, cobalt alloys, cobalt compounds, cobalt single atom and molecular catalyst configurations, we firstly establish correlations between atomic-scale structural features and catalytic performance in a coordination environment perspective for NO3RR, including the dynamic reconstruction during operation and its impact on active site. Synergizing experimental breakthroughs with computational modeling, we decode mechanisms underlying competitive hydrogen evolution suppression, intermediate adsorption-energy optimization, and durability enhancement in complex aqueous environments. The development of cobalt-based catalysts was summarized and prospected, and the emerging opportunities of machine learning in accelerating the research and development of high-performance catalysts and the configuration of series reactors for scalable nitrate-to-ammonia systems were also introduced. Bridging surface science and applications, it outlines a framework for designing multifunctional electrocatalysts to restore nitrogen cycle balance sustainably. Highlights: 1 This review covers almost all cobalt-based electrocatalysts for nitrate reduction reaction (NO3RR), including metallic cobalt, cobalt alloys, cobalt compounds, cobalt single-atom and molecular catalysts, etc. 2 The mechanism of enhancing the NO3RR performance by suppressing the hydrogen evolution reaction, as well as the durability and degradation processes, was discussed from the perspective of the electronic structure and adsorption behavior. 3 The influence of different coordination environments of Co active sites on NO3RR performance was discussed, including different isomorphic forms of the same elements around Co, different types of elements, doping of trace elements, and in situ evolution of constituent elements, etc.